STUDY OF KINETIC AND EQUILIBRIUM MODELS IN THE ADSORPTION OF ORANGE-FLAVORED SOFT DRINK ON PAPER TOWELS: A SEMIQUANTITATIVE MODEL - Dos Santos, Hubert André Nunes; dos Reis, Renan Gustavo Coelho de Souza (Seven Editora, 2026)
The understanding of concepts approached from a physicochemical perspective, whether kinetic or thermodynamic, in the classroom through calculations without conceptual visualization can represent, for most students, a major abstract paradigm. Thus, the possibility of using a common process in various activities—from its application in homemade filters to wastewater treatment—is highlighted. Adsorption was explored in the present study as a semi-analytical demonstrative approach for obtaining values of kinetic parameters present in the Arrhenius equation, as well as for determining classical thermodynamic quantities. The process occurred through the adsorption of orange-flavored soft drink (considering the beverage as a dye) onto paper towels, studying adsorption in the UV–Vis region of the electromagnetic spectrum. Initially, the absorption spectrum profile was verified, and a maximum value of 481 nm was found. Based on this result, dilutions were used to construct a calibration curve, observing a linear correlation. The equilibrium time, yield, and adsorption capacity at each determined time were studied under constant agitation of 150 rpm and variable temperatures of 25 °C, 35 °C, and 45 °C. The mechanisms studied were pseudo-first-order, pseudo-second-order, and the Elovich model, enabling the determination of kinetic parameters. Experiments carried out with different initial concentrations, monitored until equilibrium, allowed for the evaluation of the Langmuir and Freundlich models, together with thermodynamic data. DOI: https://doi.org/10.56238/sevened2026.008-043